2001
DOI: 10.1071/ea00077
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to polyethylene mulch film — a field assessment of transported materials in capsicum (Capsicum annuum L.)

Abstract: Materials used as mulches may be either transported to the farm then laid on the soil surface or grown in situ. To assess biodegradable alternatives to non-degradable polyethylene film, the response of capsicum (Capsicum annuum L. cv. Target) grown in soil beds covered with hessian (burlap), hardwood sawdust, sugarcane (Saccharum spp.) trash, paper film, black biodegradable polymer film, white polyethylene film, or left uncovered was investigated in a field trial during the autumn–winter growing season in subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Increased soil temperature beneath bioplastic films relative to bare soil has been demonstrated in previous studies (Larsson and Båth, 1996;Olsen and Gounder, 2001). However, less is known about the effect of biofabrics on soil temperature.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Increased soil temperature beneath bioplastic films relative to bare soil has been demonstrated in previous studies (Larsson and Båth, 1996;Olsen and Gounder, 2001). However, less is known about the effect of biofabrics on soil temperature.…”
Section: Discussionmentioning
confidence: 76%
“…Wheat straw and chopped newspaper waste can suppress weeds when applied in a thick layer (>7.6 cm), but this benefit is accompanied by substantially cooler soil temperatures early in the growing season (Monks et al, 1997;Larsson and Båth, 1996;Warnick et al, 2006). Unfortunately, reduced soil temperature beneath organic mulches can lead to reductions in crop yield (Olsen and Gounder, 2001). In addition to these agronomic drawbacks, organic mulches can be difficult and costly to apply on a commercial scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the loss of mechanical strength and partial conversion into CO 2 for BDMs when buried in soil or placed at the water-air surface [1,3,[13][14][15][16][17][18]. But, BDMs also have undesirable attributes, including high price (2.5 9 conventional polyethylene mulches) [19], an uncontrollable and unpredictable onset and rate of biodegradation [20], and low biobased content (e.g., PBAT and PBS are mainly derived from fossil fuel feedstocks) [2,12,21]. Due to the inclusion of fossil fuel-based components, BDMs have been labelled as ''synthetics'' and therefore are not allowed for use in US certifiable organic agriculture [8,22].…”
Section: Introductionmentioning
confidence: 99%